Attachment of Salmonella enterica on Mangoes and Survival Under Conditions Simulating Commercial Mango Packing House and Importer Facility - Mathew, Elza N.; Muyyarikkandy, Muhammed S.; Kuttappan, Deepa; Amalaradjou, Mary Anne (Frontiers in Microbiology, 2018)
Consumption of raw mangoes has led to multiple Salmonella-associated foodborne outbreaks in the US. Although several studies have investigated the epiphytic fitness of Salmonella on fresh produce, there is sparse information available on the survival of Salmonella on mangoes under commercial handling and storage conditions. Hence, the objective of the study was to evaluate the survival of Salmonella on mangoes under ambient conditions simulating the mango packing house and importer facility. Further, the ability of the pathogen to adhere and attach on to the mango fructoplane was also investigated. For the attachment assays, mango skin sections were inoculated with fifty microliters of S. Newport suspension (6.5 log CFU/skin section) and minimum time required for adhesion and attachment were recorded. With the survival assays, unwaxed mangoes were spot inoculated with the Salmonella cocktail to establish approximately 4 and 6.5 log CFU/mango. The fruits were then subjected to different storage regimens simulating fruit unloading, waxing and storage at the packing house and ripening and storage at the importer facility. Results of our study reveal that Salmonella was able to adhere on to the fructoplane immediately after contact. Further, formation of attachment structures was seen as early as 2 min following inoculation. With the survival assays, irrespective of the inoculum levels, no significant increase or decrease in pathogen population was observed when fruit were stored either at ambient (29-32°C and RH 85-95%, for 48 h), ripening (20-22°C and RH 90-95% for 9 days) or refrigerated storage (10-15°C and 85-95% for 24-48 h) conditions. Therefore, once contaminated, mangoes could serve as potential vehicles in the transmission of Salmonella along the post-harvest environment. Hence development and adoption of effective food safety measures are warranted to promote the microbiological safety of mangoes.